PENGUATAN PENDIDIKAN KARAKTER NASIONALISME MELALUI MEDIA KLIP WARNA - Melia Eka Daryati (Jurnal Abdi Insani, 2023)
Strong character will help individuals in dealing with various life situations, including maintaining and developing nationalist identity. This service aims to strengthen nationalist character education by using color clip media in early childhood. Character education and nationalism are important aspects in forming the identity and nationality of a country. However, the challenges faced are how to convey the values of character and nationalism to young children who tend to be highly influenced by the environment, social media and lack of attention to character education and nationalism. The service was carried out at the Semarak Arga Makmur Integrated Islamic Elementary School with the subjects being 1st grade elementary school children. The service method used is through material development and direct practice. Service activities are carried out in several stages including preparation, implementation and reporting. Data was collected through interviews and content analysis of color media clips. The research results show that color clip media has great potential to convey the cultivation of character and nationalism in an interesting and inspiring way. The effective use of visual, musical and narrative elements from clip media can attract attention and create an enjoyable learning experience for children. The continuation of this service activity will develop clip media content that is more diverse and relevant to the cultural and social context of Indonesian society.